2004
DOI: 10.1002/ceat.200401905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound on the Production Reaction Kinetics of Sodium Thiosulfate

Abstract: It is known that the production reaction of sodium thiosulfate which consists of the reaction of Na 2 SO 3 with sulfur is considerably slow. Ultrasound energy was used to increase the conversion fraction of sulfur and to accelerate the production reaction of Na 2 S 2 O 3 , and the effect of ultrasonic energy on the reaction kinetics was investigated. The particle size, reaction temperature, concentration of Na 2 SO 3 solution and amplitude of ultrasound power were chosen as parameters. The experiments were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The cavitation effect might improve the penetration power of alkaline or acid solution, and it could be probably reason for the high yield within short period. Ingeç and Tekin (2004) reported that the ultrasonication increases the reaction speed by increasing the effective area of reaction. However, the frequency, energy, and processing time have to be optimized to get a better quality of chitin, which can be a new avenue for the further exploration.…”
Section: Process Intensification Techniquesmentioning
confidence: 99%
“…The cavitation effect might improve the penetration power of alkaline or acid solution, and it could be probably reason for the high yield within short period. Ingeç and Tekin (2004) reported that the ultrasonication increases the reaction speed by increasing the effective area of reaction. However, the frequency, energy, and processing time have to be optimized to get a better quality of chitin, which can be a new avenue for the further exploration.…”
Section: Process Intensification Techniquesmentioning
confidence: 99%
“…(2) , a faster k can be obtained by an increase in the A value or a decrease in the E a value. For ultrasound-assisted leaching, several researchers have reported that the ultrasound treatment enhanced the rate constant of the chemical reaction by a significant increase in A [ [72] , [73] , [74] , [75] , [76] , [77] ]. Thus, the increase in the reaction rate constant for ultrasound-assisted leaching was obtained by a huge increase in A .…”
Section: Resultsmentioning
confidence: 99%
“…the dyestuffs can be removed faster and more readily from waste water. Using kinetic models, various studies have described the effect of ultrasound powers within the modified activation energy equations [30]. This study used the following modified activation energy equation to interpret the effect of ultrasound energy on the reaction.…”
Section: Figurementioning
confidence: 99%